Pengaruh Model Pembelajaran Outdoor Study Berbantuan Video Conference terhadap Kemampuan Menulis Karya Ilmiah Mahasiswa - Wolfgang Asindo Seran; Dwiyono Hari Utomo; Budi Handoyo (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research is aimed at explaining the effect of outdoor study learning model assisted by video conference toward the learners' scientific writing competence. This research used quasi experiment with two groups, they are experiment class and control class. The subjects of this research were geography learners FIS university of Negeri Malang in the academic year 2019/2020 which consisted of two classes, experiment class contained 39 learners, meanwhile control class contained 37 learners. The technique that was used to determine the class was purposive sampling. The factorial design 2x3 was also used in this research. The data was analysed by using two way anova. The results show the significant value of hypothesis test by using two way anova as large as 0,035<0,05 which meant there was an effect of outdoor study learning model assisted by video conference toward the learners' scientific writing competence. Abstrak: Penelitian ini bertujuan untuk menjelaskan pengaruh model pembelajaran outdoor study berbantuan video conference terhadap kemampuan menulis karya ilmiah mahasiswa. Penelitian ini menggunakan eksperimen semu (quasi experiment) dengan dua kelompok yaitu kelas eksperimen dan kelas kontrol. Subjek penelitian mahasiswa geografi FIS Universitas Negeri Malang tahun ajaran 2019/2020 terdiri dari dua kelas, kelas eksperimen dengan jumlah 39 mahasiswa, sedangkan kelas kontrol dengan jumlah 37 mahasiswa total 76 mahasiswa. Teknik penentuan kelas menggunakan purposive sampling. Desain faktorial 2x3 yang digunakan dalam penelitian ini. Analisis data menggunkaan two way anova. Hasil penelitian menunjukkan nilai signifikan uji hipotesis two way anova sebesar 0,035< 0,05 yang berarti ada pengaruh model pembelajaran outdoor study berbantuan video conference terhadap kemampuan menulis karya ilmiah mahasiswa.